2018
DOI: 10.1002/cssc.201702456
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Citrus Nanostructured Cellulose: A Rigorous Design‐of‐Experiment Study of the Hydrothermal Microwave‐Assisted Selective Scissoring Process

Abstract: A detailed design-of-experiment (DoE) study to investigate the cause-effect interactions of three process variables, that is, temperature (120-200 °C), holding time (0-30 min), and concentration (1.4-5.0 wt %), on the processing of citrus cellulosic matter using acid-free microwave-assisted selective scissoring (Hy-MASS) is reported. Analysis of variance (ANOVA) showed that post-microwave processing, the yield of cellulosic matter (25-72 %), decomposition temperature (345-373 °C), and crystallinity index (34-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…The trees include leaved trees, e.g., birch [33,57,58,59,60,61], and various coniferous trees [26,27,62,63,64], e.g., Pinus radiata [65]. Other trees are Acacia mangium [66], balsa [67], Syzygium cumini [68], banana pseudostem [5], palm [7,8,69], Khaya senegalensis [70], and citrus trees [71]. Nanocellulose from leaved trees is usually referred to as hardwood-derived, while nanocellulose from coniferous trees is softwood-derived.…”
Section: Introductionmentioning
confidence: 99%
“…The trees include leaved trees, e.g., birch [33,57,58,59,60,61], and various coniferous trees [26,27,62,63,64], e.g., Pinus radiata [65]. Other trees are Acacia mangium [66], balsa [67], Syzygium cumini [68], banana pseudostem [5], palm [7,8,69], Khaya senegalensis [70], and citrus trees [71]. Nanocellulose from leaved trees is usually referred to as hardwood-derived, while nanocellulose from coniferous trees is softwood-derived.…”
Section: Introductionmentioning
confidence: 99%
“…Matharu et al and de Melo et al reported a novel acid-free microwave hydrothermal treatment (MHT) method to obtain pseudonanocellulosic fibrils and/or nanocrystals without any additional chemicals. 20,44 Herein, the importance of this study is to explore the potential valorization of pea waste (rather than traditional wood pulp) as a source of defibrillated celluloses using twin screw extrusion as a 5 pretreatment prior to microwave hydrothermal treatment (MHT) ( Figure 1). Twin screw extrusion was selected as the pretreatment for being continuous, low cost, requiring no heat and the application of high shearing forces in the biomass 45 Pea (Pisum sativum) waste including leaves, vines, stems (haulm) was collected immediately after harvest from farmland nearby York (England, United Kingdom).…”
Section: Introductionmentioning
confidence: 99%
“…When lignocellulosic biomass is exposed to MAH heating, swelling and fragmentation occur within the biomass, resulting in the disruption of the lignocellulosic structure. This consequently results in an increase of surface area, decreases in the degree of polymerization and crystallinity of cellulose, and the depolymerization of lignin, which ultimately improves the accessibility of BCLs [43]. Therefore, IL-MAH was the best method to extract FBCL from S. chinensis fruit which extraction efficiency up to 4.12±0.37 mg g −1 (Fig 9).…”
Section: Chemical Changes In the Cell Walls Of S Chinensis Fruit Aftmentioning
confidence: 97%